Water Resource Development Plan for Rural Development: A Geospatial Solution - Simhachalam, Alajangi; Rao, P. Kesava; Amminedu, E; Prakash, A.J. (International Journal of Computer Sciences and Engineering, 2025)
The present study is to examine the potential for water harvesting and conservation of ground water against drought in Moinabad Mandal of Rangareddy district of Telangana (India). The Climate of the Block is characterized by a hot summer and is generally dry except during the South west monsoon season. Water resources development plan needs better understanding about the various natural resources their relations with each other and their relations with livelihood of the stakeholders. In order to optimum utilize the existing natural resources like land, vegetation and water in a selected area, proper scientific surveys should be conducted. These include mapping of soils, hydro-geomorphic features, land use/land cover pattern, surface & ground water potential surveys in addition to gradient of the terrain particularly, slope and aspect which plays a vital role in suggesting various soil and moisture conservation measures. Based on the mapping and analysis (using GIS& RS as a powerful information tools) of these natural resources, water resource development plan has been prepared on the basis of integration of information on Geomorphology, Land use / Land cover, Drainage, Ground water Prospect map and slope. Suitable structures are suggested for surface harvesting / recharge in the study area. Based on this location priority, various water-harvesting structures have been proposed to mitigate the adverse effects of drought conditions which lead to the degradation of natural resources